1996
DOI: 10.1159/000177925
|View full text |Cite
|
Sign up to set email alerts
|

Total, Free, Short-Chain and Long-Chain Acyl Carnitine Levels in Arabian Camel Milk <i>(Camelus dromedarius)</i>

Abstract: The total, free, short-chain acyl and long-chain acyl carnitine levels were measured in milk of the Arabian camel (Cαmelus dromedarius). Significant variation in carnitine concentrations were observed in milk of the camel when compared with other mammalian milk species. The result shows that Arabian camel milk possesses a higher than usual concentration of the average percent contribution of free carnitine to total carnitine that is found in most mammalian milk species. A higher proportion of total carnitine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The results of the current study are consistent with our previous investigation that there were significant differences in carnitine concentrations in the Arabian camel when compared to those species (Alhomida et al 1995a(Alhomida et al , 1996bAlhomida 1996). Significant variation in carnitine concentrations were observed in plasma and tissues of the camel when compared to other species.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results of the current study are consistent with our previous investigation that there were significant differences in carnitine concentrations in the Arabian camel when compared to those species (Alhomida et al 1995a(Alhomida et al , 1996bAlhomida 1996). Significant variation in carnitine concentrations were observed in plasma and tissues of the camel when compared to other species.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, in the camel it is higher when compared to other species but lower than in humans (Alhomida et al 1995a). Furthermore, it has been reported that a significant variation in carnitine concentrations was observed in milk of the camel when compared to other mammalian milk species (Alhomida 1996). The results showed that a higher proportion of total carnitine was found in camel milk when compared to cow, human milk, milk formulas, however, it is lower when compared to sheep and goat milk (Alhomida 1996).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Total acid-soluble (TS) and FC carnitine concentrations were estimated as described previously, 21 whereas total (TC), short-(SC), longchain acyl (LC) and acyl (AC) carnitine levels were determined as described previously 19,20 with slight modi®cation for use in the current study. Brie¯y, for FC estimation 1 ml of PCA extract was carefully neutralized with 1 M KOH.…”
Section: Determination Of Carnitine Levelsmentioning
confidence: 99%